The National Geographic Magazine Map of Alaska : showing latest explorations by U.S. Geological Survey and U.S. Coast and Geodetic Survey. - National Geographic Society (U.S.) (National Geographic Society, 1914)
Map shows proposed and existing railroads, steamship lines, glaciers, volcanoes, telegraph and cable lines, postal routes, military reservations, settlements, missions, mining activity and mineral resources. Includes explanations. Inset: "Western Extension of Aleutian Islands." Relief shown by hachures and spot heights. Scale [ca. 5,000,000].